2005
DOI: 10.1007/s00425-005-0126-7
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Arabidopsis MAPK kinase kinase (AtMEKK1) and induction of AtMEKK1–AtMEK1 pathway by wounding

Abstract: We have constructed a series of deletion mutants of Arabidopsis MAPK kinase kinase (AtMEKK1) and obtained a constitutively active mutant, AtMEKK1Delta166, which lacks in self-inhibitory sequence of N-terminal 166 amino acids but still has substrate specificity. AtMEKK1Delta166 predominantly phosphorylates AtMEK1, an Arabidopsis MAPKK, but not its double mutant (AtMEK1T218A/S224E), suggesting that Thr-218 and Ser-224 are the phosphorylation sites. In wounded seedlings, AtMEKK1 was activated and phosphorylated i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
41
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(42 citation statements)
references
References 15 publications
1
41
0
Order By: Relevance
“…Fifteen minutes after treatment, all three phosphorylated MAPK reactive signals on the western blot became stronger, comparably across all three genotypes. Therefore, unlike MEKK1D166 (Hadiarto et al, 2006), enzyme regulation and substrate preference do not appear to be altered in mekk1-5.…”
Section: Mekk1-5 Is a Partial Loss-of-function Mutant In Mekk1mentioning
confidence: 93%
See 2 more Smart Citations
“…Fifteen minutes after treatment, all three phosphorylated MAPK reactive signals on the western blot became stronger, comparably across all three genotypes. Therefore, unlike MEKK1D166 (Hadiarto et al, 2006), enzyme regulation and substrate preference do not appear to be altered in mekk1-5.…”
Section: Mekk1-5 Is a Partial Loss-of-function Mutant In Mekk1mentioning
confidence: 93%
“…The mekk1-5 mutation is within the first 166 amino acids of MEKK1, a region that when deleted (MEKK1D166) results in constitutive kinase activity in a protoplast system (Hadiarto et al, 2006) and has been implicated in the control of substrate specificity of this kinase (Ichimura et al, 2006;Suarez-Rodriguez et al, 2007). The proposed function of this region raised the possibility of altered regulation and substrate specificity/preference of MEKK1 in mekk1-5.…”
Section: Mekk1-5 Is a Partial Loss-of-function Mutant In Mekk1mentioning
confidence: 99%
See 1 more Smart Citation
“…It has been previously reported that the MEKK1-MKK1-MPK4 cascade is stimulated following wounding stress (Hadiarto et al 2006;Matsuoka et al 2002). Other studies have also indicated that these cascades are involved in several other stress signalling pathways: the MEKK1-MKK2-MPK4/MPK6 cascade in salt and cold stress signalling (Teige et al 2004) or the MEKK1-MKK4/MKK5-MPK3/MPK6 cascade following pathogen infection (Asai et al 2002).…”
mentioning
confidence: 97%
“…Yeast two-hybrid analyses indicated that MPK4, MKK1, and MKK2 also interact with the stressinduced MPKKK, MEKK1 Mizoguchi et al, 1998), and MEKK1 can activate both MKK1 (Hadiarto et al, 2006) and MKK2 (Teige et al, 2004). Mutations in MEKK1 (Ichimura et al, 2006;Nakagami et al, 2006;Suarez-Rodriguez et al, 2007) result in plants morphologically similar to mpk4 mutants, including dwarfed growth, enhanced PR1 gene expression, and reduced MPK4 activity induction by hydrogen peroxide or flagellin.…”
mentioning
confidence: 99%